A carbon-free inorganic–metal complex consisting of an all-nitrogen pentazole anion, a Zn(ii) cation and H2O. Issue 41 (3rd October 2017) - Xu, Yuangang; Wang, Pengcheng; Lin, Qiuhan; Lu, Ming
Abstract : A carbon-free inorganic–metal complex [Zn(H2 O)4 (N5 )2 ]·4H2 O was synthesized in very good yield by the ion metathesis of [Na(H2 O)(N5 )]·2H2 O solution with Zn(NO3 )2 ·6H2 O. Abstract : A carbon-free inorganic–metal complex [Zn(H2 O)4 (N5 )2 ]·4H2 O was synthesized by the ion metathesis of [Na(H2 O)(N5 )]·2H2 O solution with Zn(NO3 )2 ·6H2 O. The complex was well characterized by IR and Raman spectroscopy, elemental analysis (EA), powder X-ray diffraction (PXRD), and differential scanning calorimetry (DSC). The structure of the complex was confirmed by single-crystal X-ray crystallography and a Zn(ii ) ion is coordinated in a quadrilateral bipyramid environment in which the axial position is formed by two nitrogen atoms (N1) from two pentazolate rings ( cyclo -N5 − ) and the equatorial plane is formed by four oxygen atoms (O1) from four coordinated water molecules. The thermal analysis of [Zn(H2 O)4 (N5 )2 ]·4H2 O reveals that although water plays an important role in stabilizing cyclo -N5 −, dehydration does not cause immediate decomposition of the anion. However, cyclo -N5 − decomposed into N3 − and N2 gas at 107.9 °C (onset). Based on its chemical compatibility and stability, the complex exhibits promising potential as a modern environmentally-friendly energetic material.